1985
DOI: 10.1144/gsl.qjeg.1985.018.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Geological and geotechnical considerations, associated with some sections of the M25 construction

Abstract: Introduction A joint meeting of the Engineering Group and the Institution of Highway Engineers was held at Burlington House on Tuesday, 10 January 1984. The topic of the meeting inspired practising engineers, academics and researchers alike, and this was reflected in an extremely well attended meeting. The audience listened to a number of speakers who have been actively involved with construction of particular sections of the M25 and who related their experiences in dealing with various gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On sections of the M25 on Gault in Kent the empirical correlation by Stroud (1975) of SPT Nvalues with undrained shear strengths is noted by Newman (1985) to give a better correlation with depth than conventional laboratory testing of undisturbed Kay & Parry (1982) Samuels (1975 The authors Garrett & Barnes (1984) The authors…”
Section: Undrained Shear Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…On sections of the M25 on Gault in Kent the empirical correlation by Stroud (1975) of SPT Nvalues with undrained shear strengths is noted by Newman (1985) to give a better correlation with depth than conventional laboratory testing of undisturbed Kay & Parry (1982) Samuels (1975 The authors Garrett & Barnes (1984) The authors…”
Section: Undrained Shear Strengthmentioning
confidence: 99%
“…Newman (1985) observed that prior to the construction of the M25 and M26 Motorways in Kent the Gault Clay exposure was mainly pastureland and woodland probably reflecting the historical appreciation of its high shrinkage and swelling properties. There has been a high incidence of house damage insurance claims in recent years related to shrinkage problems.…”
Section: Site Investigation Practices For Foundations In Gault Claysmentioning
confidence: 99%